BULLYING DAN SOLUSINYA DALAM AL-QUR’AN - Sindy Kartika Sari (Academic Journal of Islamic Principles and Philosophy, 2020)
Bullying has become a habit in the community. Making fun of, ridiculing, demeaning, insulting, and all sorts of acts of hurt to others. Act like this have existed since ancient times, even the prophets also experienced acts of bullying. This article focuses on studying the Qur'an's message about bulliying and its solution with thematic interpretation methods. Some verses that contain word meanings such as yakhsar, istahza’a, and their derivatives are collected, then analyzed the purpose of the verses. The results of this study indicate that some verses of the Qur’an indicate that bullying had indeed occurred in earlier times, even before the Qur’an was revealed to the Prophet Muhammad. The process of bullying told by the Qur'an is indeed diverse. But through the stories in the Qur'an, can be learned for contemporary life. Solutions to bullying in this case are also divided into two classifications, namely solutions for perpetrators and solutions for victims of bullying. Some ways to prevent the occurrence of bullying according to the message of the Qur’an, among others by increasing taqwa, saying good things, calling with good calls. This research has contributed in expanding the scope of the study of thematic interpretation of the Qur'an.